Evaluating supplier quality performance using analytical hierarchy process - Kalimuthu Rajoo, Shanmugam Sundram; Mat Kasim, Maznah; Ahmad, Nazihah (2013)
This paper elaborates the importance of evaluating supplier quality performance to an organization.Supplier quality performance evaluation reflects the actual performance of the supplier exhibited at customer's end.It is critical in enabling the organization to determine the area of improvement and thereafter works with supplier to close the gaps.Success of the customer partly depends on supplier's quality performance.Key criteria as quality, cost, delivery, technology support and customer service are categorized as main factors in contributing to supplier's quality performance.18 suppliers' who were manufacturing automotive application parts evaluated in year 2010 using weight point system.There were few suppliers with common rating which led to common ranking observed by few suppliers'.Analytical Hierarchy Process (AHP), a user friendly decision making tool for complex and multi criteria problems was used to evaluate the supplier's quality performance challenging the weight point system that was used for 18 suppliers'.The consistency ratio was checked for criteria and sub-criteria.Final results of AHP obtained with no overlap ratings, therefore yielded a better decision making methodology as compared to weight point rating system.